Effect of nitrogen fertilization levels and plant density on dry weight, yield components and bulb quality of onion plant - Ehab ATTAYA; Abd-Allah BARDISI; Ali OSMAN; Hany ISMAIL; Khairiah M. ALWUTAYD; Wasimah B. AL-SHAMMARI; Nadi A. AL-HARBI; Salem M. AL-QAHTANI; Sabreen IBRAHEM; Khaled ABDELAAL (Notulae Botanicae Horti Agrobotanici Cluj-Napoca, 2024)
A field experiment was carried out during the two successive winter seasons of 2020/2021 and 2021/2022 to study the effect of mineral nitrogen levels and plant density on dry weight, yield and its components, as well as bulb quality of onions (cv. ‘Ahmar Tanawy’). This experiment included 12 treatments, which were combinations between four levels of mineral nitrogen (0, 192, 240 and 288 kg N/ha) and three plant densities (4, 5 and 6 rows/ridge equal 33.33, 41.67 and 50 plants/m2, respectively). These treatments were arranged in a split-plot design with three replications. Nitrogen levels were randomly arranged in the main plots, and plant densities were randomly distributed in the subplots. Nitrogen application at 192,244 and 288 kg N/ha led to increase dry weight/plant compared to control (zero N) and 288 kg N/ha gave the highest values of dry weight of leaves, dry weight of bulbs, and total dry weight per plant at 100 days in both seasons. The increases in total dry weight per plant were about 4.84 and 4.80 g per plant for 192 kg N/ha, 4.76 and 3.87 g per plant for 244 kg N/ha, and 6.86 and 5.74 g per plant for 288 kg N/ha over the control at 100 days in the 1st and 2nd seasons, respectively. The interaction between N at 288 kg/ha and low plant density (4 rows/ridge) gave the highest values of dry weight of leaves, bulb, and total dry weight/plant and increased yield of grade 1, exportable yield, average bulb weight, as well as nitrate and sulphur contents in bulbs, whereas the interaction between N at 244 kg/ha and high plant density (6 rows/ridge) increased grades 2, 3, and 4, marketable yield, and total yield/ha.